Exploring the Effectiveness of Self-Healing Butterfly Technique for Anxiety Management: A Systematic Review - Tata Mahyuvi; Sukma Cahya Ramadhan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The study aims to analyze the effects of butterfly hug therapy on anxiety levels through a systematic review of relevant studies. Journal searches were conducted using Semantic Scholar and Google Scholar, focusing on articles published between 2020 and 2024 in English and Indonesian. Inclusion criteria required full-text accessibility in PDF format, with keywords combining "Anxiety OR Anxiety Disorder" AND "Butterfly hug OR Butterfly hug Therapy" applied consistently across databases. After screening, eight studies met the criteria and were systematically reviewed.  Butterfly hug therapy is identified as a simple, cost-effective, and accessible intervention that significantly reduces anxiety levels across various populations. The included studies highlighted its efficacy in managing anxiety caused by medical stress, academic challenges, and other stressors. By integrating rhythmic, bilateral physical stimulation, butterfly hug therapy helps individuals achieve emotional regulation and a sense of comfort, making it a versatile tool for anxiety management.  This review concludes that butterfly hug therapy is a promising non-pharmacological intervention for reducing anxiety, emphasizing its potential for broader application in clinical and community settings.